Change in Quality of Life after a Cancer Diagnosis among a Nationally Representative Cohort of Older Adults in the US. (9th August 2019) - Schwartz, Rebecca M.; Ornstein, Katherine A.; Liu, Bian; Alpert, Naomi; Bevilacqua, Kristin G.; Taioli, Emanuela
Abstract: Age-related decreases in Quality of Life (QoL) are often compounded by comorbidities, including cancer. This study aimed to examine QoL changes before and after a new cancer diagnosis using data from the National Health and Aging Trend Study (NHATS), linked to Medicare claims ( N  = 136). There was a significant increase in the relative odds of fair/poor self-reported health and needing help with Activities of Daily Living. There was also a marginal increase in depression, but no change in anxiety or pain scores. Results underscore importance of considering pre-cancer QoL when making treatment decisions for older adult cancer patients.